Transformative Authentic Assessment for Learner Identity Reconstruction in Personalized Learning Pathways: Advancing SDG 4 and SDG 10 in Indonesian Education - Afakhrul Masub Bakhtiar; Yatim Riyanto; Sujarwanto Sujarwanto (Journal of Current Studies in SDGs, 2026)
Objective: To investigate how transformative authentic assessment implemented within Personalized Learning Pathways (PLP) reconstructs learner identity by enhancing motivation and self-efficacy among learners in Indonesian Community Learning Centers (PKBM), while supporting the achievement of Sustainable Development Goals (SDGs) 4 and 10. Method: A qualitative multi-site case study was conducted at PKBM Sekolah Dolan Malang and PKBM Tsurayya Karimah Indonesia. Fifty-seven participants, including institutional heads, tutors, administrative staff, learners, and an external supervisor, were purposively selected. Data were collected through participatory observations, semi-structured interviews, and document analysis. The data were analyzed using thematic analysis and cross-site synthesis to identify recurring patterns across both learning centers. Results: The findings reveal that authentic assessment functions as a continuous, reflective, and learner-centered process rather than merely an instrument for measuring academic achievement. Portfolio-based assessment, reflective discussions, individualized feedback, and continuous learning monitoring significantly enhanced learners' intrinsic motivation and self-efficacy. These assessment practices gradually transformed learners' perceptions from educational failure and low self-confidence toward positive learner identities characterized by confidence, autonomy, responsibility, and lifelong learning orientation. Novelty: Proposing a transformative authentic assessment framework that conceptualizes learner identity reconstruction as a sequential psychological process linking authentic assessment, recognition of learners' strengths, enhanced motivation, strengthened self-efficacy, and positive learner identity. The findings extend authentic assessment literature beyond academic achievement by demonstrating its role as a psychological mechanism for educational inclusion and learner empowerment within personalized learning pathways in community education.